Quality of Life of Cancer Patients In A Cancer Hospital of Chitwan - Gurung, Sunita; Rai, Lalita (Nepalese Journal of Cancer, 2024)
Introduction: Cancer is the third leading cause of death in developing countries and is appearing indistinctly public health catastrophe. Quality of Life (QoL) is one of the most important patient-reported outcomes in cancer therapy. As many studies had shown that QoL is important to be assessed but it is still lacking in it. Thus, the objective of this research was to assess quality of life of cancer patients.Methods: A descriptive cross-sectional research design was used to assess the quality of life of cancer patients in B.P. Koirala Memorial Cancer Hospital. Non-probability purposive sampling technique was adopted to collect data from 384 respondents. Structured interview schedule; European Organization for Research and Treatment of Cancer (EORTC QLQ-C30): A Quality of Life Instrument tool was used to collect data. Descriptive (mean, frequency, percentage, and standard deviation) and inferential (Whitney U test, Kruskal-Wallis H and Pearson's correlation coefficient) statistics were applied for data analysis in Statistical Package for Social Science (SPSS) version-16.Results: The finding of this study showed that more than half (63.3%) of the respondents had high quality of life. The average quality of life score for three different scales were 59.8 (global health status scale), 82.0 (functional scale) and 25.8 (symptom scale). Education, annual family income, ECOG performance status and site of cancer were found to be significantly associated with the three different quality of life scales. There was positive relation of functional scale and negative relation of symptom scale with global health status scale.Conclusion: Most of the respondents had high QoL but few of them had still low QoL. Therefore the research finding highlights the importance of provision of necessary beneficiaries for cancer patients to improve their quality of life.